Ecosystem services certification: Opportunities and constraints - Meijaard, E.; Sheil, Douglas; Guariguata, Manuel R.; Nasi, Robert; Sunderland, Terry C.H.; Putzel, L. (Center for International Forestry Research, 2011)
A major challenge in trading ecosystem services is the need to quantify and commoditise services, for monitoring and verification as well as for trade. This is relatively straightforward for goods such as forest honey or shade-grown coffee, but potentially complex for services such as water purification, reducing risk from floods or other disasters or carbon sequestration. Developing certification systems for forest ecosystem services is one potential way to define, quantify and verify these services in a way that buyers can trust, and this is why certification of ecosystem services is promoted by a number of environmental and forestry NGOs. Certification of ecosystem services is a useful concept, but many practical and theoretical obstacles must be addressed before it can be put into practice. This paper is a review of existing development in certification of ecosystem services, with information useful for designing and implementing projects to evaluate the efficacy of new systems. We discuss the potential use of more holistic concepts for measuring management sustainability, which are to date undeveloped and untested, and recommend developing pilot projects that are specifically designed to address a number of challenges inherent to ecosystem service certification.